Search for CP violation in the decays D(0)-> K(-)K(+) and D(0)->pi(-)pi(+) - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2008)
We measure time-integrated CP-violating asymmetries of neutral charmed mesons in the modes D0→K-K+ and D0→π-π+ with the highest precision to date by using D0→K-π+ decays to correct detector asymmetries. An analysis of 385.8fb-1 of data collected with the BABAR detector yields values of aCPKK=(0.00±0.34(stat)±0.13(syst))% and aCPππ=(-0.24±0.52(stat)±0.22(syst))%, which agree with standard model predictions. © 2008 The American Physical Society.